Comparison of the extracellular full-length and truncated recombinant protein A production in Escherichia coli BL21 (DE3) - Rigi, Garshasb; Beyranvand, Parisa; Ghaedmohammadi, Samira; Heidarpanah, Sara; Akbari Noghabi, Kambiz; Ahmadian, Gholamreza (Archives of Advances in Biosciences, 2015)
Protein A is a commercially important protein in biotechnological and medicinal applications. The great value of this protein and its applications in genetic and protein engineering and microbial researches as well as the growing use in biochemical industries, biotechnology, medicine and pharmacology, highlight the importance of the present study. In this survey the encoding genes of full-length and truncated forms of protein A were expressed in E. coli under an optimized expression condition. Optimization of the culture conditions resulted in an increase in expression and secretion of both forms of the protein, the pattern of expression and secretion levels for two forms was completely different. A minimum of 10-fold higher expression was observed for the truncated protein in comparison to that of the full-length recombinant form. Hydropathy plot of both forms of proteins showed that the missing domains in the truncated form contain groups of amino acids with high hydrophobicity score. Deletion of the terminal region could led to a higher expression level of the recombinant protein in E. coli. The function of these two proteins was studied using ELISA, which showed a higher activity for the truncated form for binding to IgG, compared to the full-length protein.